AB1104 Influence of Sociodemographic and Clinical Factors in Health Related Quality of Life in Patients Followed in a Rheumatology Day-Care Unit. (9th June 2015) - Raposo, A.; Sousa Neves, J.; Cerqueira, M.; Teixeira, F.; Peixoto, D.; Costa, J.; Alcino, S.; Afonso, C.
Abstract : Background: The health-related quality of life (HRQL) is an important indicator of the burden of inflammatory rheumatic diseases (IRD). Their outcomes may also be affected by coexisting chronic conditions that can cause functional impairment and activity limitation with significant reductions in HRQL. Objectives: To determine the health status and quality of life in patients with IRD followed in a rheumatology day-care unit and to identify associated demographic and disease-related parameters influencing it. Methods: The Health Assessment Questionnaire (HAQ) to assess impairment in daily activities due to illness and Short Form-36 (SF-36) to assess HRQL were applied to patients on day-care routine visits. Disease activity clinical measures (DAS28-ESR, ASDAS-PCR, mean pain on VAS) were collected according to the disease and the predominant involvement. A p value of <0.05 was considered as significant. Results: A total of 84 patients were consecutively included, predominantly female (59.5%), with a mean age of 46.25±13.25 years (range 19-85) and a mean disease duration of 14.62±8.07 years (1-38). Thirty six (42.9%) patients had rheumatoid arthritis and 48 (57.1%) had spondylarthritis. Seventy seven (91.7%) patients with current bDMARDS, 51 (60.7%) also with cDMARDS and 19 (22.6%) with low doses corticosteroid treatment. Twenty four (28.6%) had associated hypertension, 4 (4.8%) diabetes and 10 (11.9%) dyslipidemia. The mean DAS28-ERS was 2.59±1.06 (0.53 to 6.94), median ASDAS-PCR 1.40±1.15 (0.20 to 5.50), mean pain on a VAS 3.77±2.58 (0 to 10), mean HAQ 0.76±0.71 (0 to 2.88) and mean SF-36 418.71±162.31 (103.50 to 707). Strong correlation ( p <0.01) was found between high scores of HAQ and low SF-36. These scores correlated also with older age, high pain on a VAS and high disease activity measured by ASDAS-PCR and DAS28-ESR. Longer disease duration correlated as well with lower level of SF-36 ( p <0.05), but not with HAQ. Rheumatoid arthritis showed significant higher levels of HAQ than spondylarthritis. The female gender, current corticosteroid treatment and history of hypertension were associated both with higher HAQ and lower SF-36 ( p <0.05). The scores were not statistically different between bDMARDS or cDMARDS, smoking and alcohol consumption, civil or employment status, level of education or other associated diseases. Conclusions: Our findings suggest that not only the activity or duration of the disease, but also the gender, concomitant comorbidities and therapies can influence the HRQL and daily activities. The disease activity could be a determinant of disability but is important to incorporate coexisting conditions and demographic data in the evaluation of HRQL. Disclosure of Interest: None declared